A Chemical Screen Identifies Compounds Limiting the Toxicity of C9ORF72 Dipeptide Repeats. Issue 2 (21st February 2019) - Corman, Alba; Jung, Bomi; Häggblad, Maria; Bräutigam, Lars; Lafarga, Vanesa; Lidemalm, Louise; Hühn, Daniela; Carreras-Puigvert, Jordi; Fernandez-Capetillo, Oscar
Summary: The expansion of GGGGCC repeats within the first intron of C9ORF72 constitutes the most common cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Through repeat-associated non-ATG translation, these expansions are translated into dipeptide repeats (DPRs), some of which accumulate at nucleoli and lead to cell death. We here performed a chemical screen to identify compounds reducing the toxicity of ALS-related poly(PR) peptides. Our screening identified sodium phenylbutyrate, currently in clinical trials, and BET Bromodomain inhibitors as modifiers of poly(PR) toxicity in cell lines and developing zebrafish embryos. Mechanistically, we show that BET Bromodomain inhibitors rescue the nucleolar stress induced by poly(PR) or actinomycin D, alleviating the effects of the DPR in nucleolus-related functions such as mRNA splicing or translation. Our work suggests that BET Bromodomain inhibitors might have beneficial effects in diseases linked to nucleolar stress such as ALS/FTD. Graphical Abstract: Highlights: A chemical screen to counteract the toxicity of ALS-related PR20 peptides Bromodomain and HDAC inhibitors rescue the viability of cells exposed to PR20 PFI-1 and Na-Phen increase survival in PR20 -treated developing zebrafish Bromodomain inhibitors rescue nucleolar stress induced by PR20 or actinomycin D Abstract : By conducting a cell-based phenotypic screen, Corman and colleagues identify compounds reducing the toxicity of poly(PR) peptides, which have been associated to the main genetic cause of ALS and FTD. The work also reveals a general effect of Bromodomain inhibitors in counteracting nucleolar stress.